The Effects of Sevoflurane vs. Propofol for Inflammatory Responses in Patients Undergoing Lung Resection: A Meta-Analysis of Randomized Controlled Trials - Yuan, Jing-Li; Kang, Kang; Li, Bing; Lu, Jie; Miao, Meng-Rong; Kang, Xia; Zhang, Jia-Qiang; Zhang, Wei (Frontiers in Surgery, 2021)
Objective: Inflammatory cytokines are increased during one-lung ventilation in patients undergoing lung resection, and this increase can be fatal. Propofol and sevoflurane are the main anesthetics used for these patients. Unfortunately, there is no consensus on the best choice of an anesthetic agent concerning an inflammatory response in patients undergoing lung resection. This meta-analysis aimed to compare the effects of propofol and sevoflurane on the inflammatory response in patients undergoing lung resection. Methods: We searched electronic databases to identify randomized controlled trials comparing the effects of different anesthetics (sevoflurane vs. propofol) on the inflammatory response. The primary outcome concerned the concentration of systematic inflammatory cytokines. The secondary outcomes concerned the concentrations of inflammatory cytokines in the bronchoalveolar lavage (BAL) fluid from the dependent and independent lung. Random effects analysis of the meta-analyses were performed to synthesize the evidence and to assess the concentrations of inflammatory factors in the sevoflurane and propofol groups. Results: Eight trials involving 488 participants undergoing lung resection with one-lung ventilation were included. There was no significant difference in the concentrations of systemic interleukin (IL)-6, IL-10, or tumor necrosis factor α between the sevoflurane and propofol groups. Compared with the propofol group, BAL levels of IL-6 in the dependent ventilated lung were decreased in the sevoflurane group (three trials, 256 participants; standardized mean difference [SMD], –0.51; 95% confidence interval [CI], –0.90 to –0.11; p = 0.01; I2 = 46%). The BAL levels of IL-6 in the independent ventilated lung were also decreased by sevoflurane (four trials, 362 participants; SMD, –0.70; 95% [CI], –0.93 to –0.47; p < 0.00001; I2 = 0%). Conclusions: There was no difference in the systematic inflammatory response between the sevoflurane and propofol groups. However, compared with propofol, sevoflurane can reduce the local alveolar inflammatory response.